2003
DOI: 10.1074/jbc.m302571200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Human Receptor Activity-modifying Protein 1 Domains Responsible for Agonist Binding Specificity

Abstract: When co-expressed with receptor activity-modifying protein (RAMP) 1, calcitonin receptor-like receptor (CRLR) can function as a receptor for both calcitonin gene-related peptide (CGRP) and adrenomedullin (AM). To investigate the structural determinants of ligand binding specificity, we examined the extracellular domain of human (h) RAMP1 using various deletion mutants. Co-expression of the hRAMP1 mutants with hCRLR in HEK-293 cells revealed that deletion of residues 91-94, 96 -100, or 101-103 blocked [ 125 I]C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…This discrepancy could be due in part to interference by the extra N-terminal tyrosine residue (Tyr 0 ). In any event, the contribution of the RAMP1 C-tail to CGRP potency is much smaller than that made by its extracellular domain (13,17,32,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy could be due in part to interference by the extra N-terminal tyrosine residue (Tyr 0 ). In any event, the contribution of the RAMP1 C-tail to CGRP potency is much smaller than that made by its extracellular domain (13,17,32,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…They then mediate the transport of CRLR to the cell surface, where the heterodimers form functional CGRP or AM receptors: CRLR/RAMP1 forms the CGRP 1 receptor (4), which can also be activated by high concentrations of AM (7,8); CRLR/RAMP2 forms an AM-specific receptor that is sensitive to the AM receptor antagonist AM-(22-52) (AM 1 receptor) (7,9); and CRLR/RAMP3 forms an AM receptor that is sensitive to both the CGRP 1 receptor antagonist CGRP-(8 -37) and AM-(22-52) (AM 2 receptor) (7,9). It is the RAMP extracellular domain that mediates agonist binding to CRLR/RAMP heterodimers (11)(12)(13), which in turn mediate intracellular cAMP production and Ca 2ϩ mobilization (4,10).…”
mentioning
confidence: 99%
“…These data suggest that a single orthologous gene of CTR/CLR existed in a common ancestor of chordates and that this gene was duplicated to CTR and CLR in the vertebrate lineage. Bf-RAMP-LPs possessed four Cys residues and a transmembrane domain, which are crucial for the biochemical functions of vertebrate RAMPs (43)(44)(45)(46). Furthermore, prediction of the secondary structure of Bf-RAMP-LPs demonstrated that, similar to vertebrate RAMPs, they possess three ␣-helical regions (Fig.…”
Section: Distinct Tissue Distribution Of Gene Expression Of Ct/cgrp Fmentioning
confidence: 99%
“…The RAMPs interact via their NH 2 terminus 23 with the calcitonin receptor-like receptors to produce a different receptor specificity by influencing the formation of the receptor pocket by allosteric modulation. 24 The biological actions of CGRP are mediated predominantly through the CGRP 1 receptor, which is made up of the calcitonin receptor-like receptors and RAMP1 proteins, both of which have been demonstrated within the endothelium and underlying smooth muscle cells of human fetoplacental vessels. 13,14 Unlike classic vasodilators, CGRP elicited cardiovascular responses, which were particularly long-lasting.…”
Section: Thakor and Giussani Cgrp And Fetal Cardiovascular Regulationmentioning
confidence: 99%